A Hybrid Digital Watermarking Approach Using Wavelets and LSB - Kumar, V. Ashok; Dharmaraj, C.; Rao, Ch. Srinivasa (Bulletin of Electrical Engineering and Informatics, 2017)
The present paper proposes a novel approach called Wavelet based Least Significant Bit Watermarking (WLSBWM) for high authentication, security and copyright protection. The present approach utilizes Alphabet Pattern (AP) approach generating shuffled image in the first stage and Pell’s Cat Map (PCM) is used for providing more security and strong protection from attacks. PCM applies on each 5×5 sib images. A wavelet concept is used to reduce the dimensionality of the image until it equals to the size of the watermark image.  Apply the Discrete Cosign Transform in the first stage later applies N levels Discrete Wavelet Transform (DWT) for reducing up to the size of the watermark image. Insert the water mark image in LHn Sub band of the wavelet image using LSB concept. Simulation results show that proposed technique produces better PSNR and similarity measure. The experimental results indicate that present approach is more reliable and secure efficient.The robustness of the proposed scheme is evaluated against various image-processing attacks.